Are medium-sized cities strong nodes in the settlement system? Demographic trends of Italian provincial capitals from 2000 to the Covid-19 pandemic - Clerici, Maria Antonietta. Autor (IGiPZ PAN, 2022)
Medium-sized cities are an important component of the settlement system and are often described as a joining link between urban and rural areas. However, in recent decades they have been impacted by growing competition from large cities which have tremendous appeal for the post-Fordist economy and for various segments of the population. This paper analyses the demographic trajectories of 99 medium-sized cities in Italy with provincial capital status, from the beginning of the twenty-first century to the outbreak of the COVID-19 pandemic. Over a twenty-year period marked by many difficulties for the Italian economy in an international context, what has the demographic performance of these cities been? The research addresses two areas. On the one hand, it analyses the demographic vitality of the provincial capitals compared to the metropolitan centres; on the other, it follows the redistribution of populations in the provincial capitals’ urban areas, which coincide with the employment areas (Sistemi locali del lavoro). Significant behavioural discontinuities emerge between the decade of 2000-2010 and the following decade, which was characterised by a gradual recovery after the shock of the Great Recession. The picture was changed further by the COVID-19 pandemic. Furthermore, persistent differences between the medium-sized cities of Northern and Southern Italy stand out, but so do new internal divisions within the country, reframing this historical dualism.
24 cm
Keywords: miasta średniej wielkości; stolice prowincji; dynamika demograficzna; obszary zatrudnienia; Wielka Recesja; COVID-19; Włochy